A belief revision approach for argumentation-based negotiation agents - Pilotti, Pablo; Casali, Ana; Chesnevar, Carlos (Zielona Góra: Uniwersytet Zielonogórski)
Negotiation is an interaction that happens in multi-agent systems when agents have conflicting objectives and must look for an acceptable agreement. A typical negotiating situation involves two agents that cannot reach their goals by themselves because they do not have some resources they need or they do not know how to use them to reach their goals.
Keywords: argumentation-based negotiation; collaborative agents; belief revision; multi-agent system